A Decision Support System for Fertilization Recommendations for Oil Palm Using the AHP Method Based on Plant Vegetative Conditions - Karolus Liyudanus; Suraya Suraya; Nuniek Herawati (Journal of Engineering, Electrical and Informatics, 2026)
Palm oil is a vital commodity for the Indonesian economy, but improper fertilization often leads to waste, reduced yields, and negative environmental impacts. The objective of this research is to develop a Decision Support System (DSS) for palm oil fertilization recommendations using the Analytical Hierarchy Process (AHP) method, based on the plant's vegetative condition, soil condition, and climate. Therefore, a systematic, data-driven approach is needed for fertilization optimization. This DSS is designed to address these challenges by using three main kriteria: the plant's vegetative condition, soil condition, and climate condition. The AHP method is used to assess and prioritize these kriteria, resulting in more accurate fertilization recommendations that are tailored to the field conditions. This system is expected to assist farmers and plantation managers in making more informed, efficient, and effective fertilization decisions, which will ultimately increase crop productivity and reduce negative environmental impacts. This research successfully designed and implemented a DSS for oil palm fertilization recommendations. The AHP method was successfully applied to structure the problem, determine criteria weights, and provide agronomically valid recommendations through case study testing. The test results demonstrated that the system was capable of providing logical and useful recommendations for both nutrient deficiency conditions and optimal land conditions.